ANALISIS KESESUAIAN RENCANA KELOLA DI KESATUAN PENGELOLAAN HUTAN PRODUKSI (KPHP) DAMPELAS TINOMBO - Possumah, Virginia Christina; Akhbar, Akhbar; Golar, Golar (Universitas Tadulako, 2014)
The purpose of this study was to know compatibility planning documents of forest production management with techniques and field conditions. The research was conducted at Production Forest Management Unit (KPHP) Model Dampelas Tinombo, Donggala Regency, Central Sulawesi. Study was done by survey and explorative-description methods with qualitative approach. The results showed that documents of forest production management of KPHP Model Dampelas Tinombo compatible with Pedoman Petunjuk Teknis Dirjen Planologi Kehutanan Nomor: P.5/VII-WP3H/2012. Further, communities had high understanding on the planning of forest production management of KPHP Model Dampelas Tinombo. Keywords: Compatibility, Management planning, Production Forest.